PATH-28. THE NATURAL HISTORY OF BRAF V600E-MUTATED GLIOBLASTOMAS IN ADULTS. (5th November 2018) - Schreck, Karisa; Vera, Elizabeth; Aboud, Orwa; Acquaye, Alvina; Boris, Lisa; Briceno, Nicole; Brown, Miranda; Chung, Hye-Jung; Crandon, Sonja; Garren, Nancy; Ji, Ming; Levine, Jason; et al.
Abstract: BACKGROUND: BRAF V600E-mutations are rare but noteworthy in primary brain tumors given their potential as a targetable mutation and the lack of efficacious therapies for glioblastoma. BRAF V600E mutations may serve as a prognostic marker in pediatric and low-grade gliomas, and are associated with improved survival in young adults with glioblastoma; however, its prognostic significance in adults >35 years is uncertain given the very small number of patients evaluated to date. METHODS: Patients aged >18 with WHO III-IV glioma and a BRAF V600E mutation were identified from the National Institutes of Health, the Johns Hopkins Hospital, and a previous publication (PMID:27503138). Paired control cases were identified at each institution based on age, sex, degree of resection, performance status at diagnosis/first encounter, MGMT and IDH status, and first-line treatment. Log-rank test was used to compare survival curves. RESULTS: The present cohort consisted of 23 patients (6 from each institution and 11 from a published cohort) with median age of 39 (range 20–70 years), 78% female, and 87% with a glioblastoma diagnosis. No tumors had an IDH mutation. 39% of patients were aged >50 years. All but one were treated with radiation and temozolomide at diagnosis (exception went into hospice and died shortly thereafter). The median overall survival was 33.4 ± 8.4 months in all patients. For 13 patients aged 35 or older, median survival was 34.5 ± 12.1 months compared to 18.0 ± 3.0 months in case-matched controls (p=0.03). Two patients were treated with dabrafenib and trametinib; one is still on therapy (26 months), the other progressed after 8 months. CONCLUSIONS: Adults aged >35 with BRAF V600E mutation may have improved survival compared with matched controls, similar to results in young adults. BRAF V600E mutations occur in patients with glioblastoma aged >50 years and testing in this population should be considered as well.